Perencanaan LTE-A untuk Heterogeneous Network dengan Metode CADS4 di Grand Asia Afrika - ARIYANTO, YOGI; PUTRI, HASANAH; NOVIANTI, ATIK (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2021)
ABSTRAKBerdasarkan hasil pengukuran di Grand Asia Afrika (GAA) diketahui terdapat peningkatan kualitas jaringan setelah pemasangan unit COMBAT selama 7 hari. RSRP ≥ -95 dBm sebelumnya sebesar 75,70% menjadi 100%, SINR ≥ 0 dB dari 53,58% menjadi 97,54%, dan throughput ≥ 8 Mbps sebelumnya sebesar 48,12% menjadi 89,55%. Untuk mempertahankan kualitas tersebut maka dibangunlah small cell. Perencanaan menerapkan metode inter-band carrier aggregation pada heterogen network LTE dengan skema CADS4 sebagai pengganti unit COMBAT. Tujuan perencanaan ini adalah extended throughput dan agar kualitas layanan pada beban trafik tinggi tetap baik. Macro cell sebagai Primary Cell (PCell) pada band-1 2100 MHz dan micro cell sebagai Secondary Cell (SCell) pada band-3 1800 MHz. Hasil perencanaan menunjukkan telah memenuhi standar RF Parameter LTE yaitu RSRP sebesar -92,65 dBm, SINR sebesar 16,55 dB, throughput sebesar 1,062 Mbps, dan user connected 97%.Kata kunci: LTE-A, heterogen network, CADS4, Great Asia Afrika Bandung ABSTRACTBased on the report on the development of temporary sites in the tourist area of Great Asia Africa (GAA), it shows that the DRR rate is> 90% in the sectors leading to GAA. From the measurement, it is known that there is an increase in network quality after installing the COMBAT unit for 7 days. For RSRP ≥ -95 dBm, the previous amount was 75.70% to 100.00%, for SINR ≥ 0 dB previously it was 53.58% to 97.54%, and for throughput ≥ 8 Mbps the previous was 48.12% to 89,55%. To maintain the quality of the network, small cells were built to cover the GAA area. Planning to apply the inter-band carrier aggregation method to the heterogeneous LTE network with the CADS4 scheme to replace the COMBAT unit. The purpose of planning is to provide extended throughput and so that the service quality at high traffic loads remains good. The configuration used is a macro cell as a Primary Cell (PCell) in the band-1 2100 MHz and a micro cell as a Secondry Cell (SCell) in the 1800 MHz band-3. The results of the planning meet the LTE parameter RF standards, RSRP of -92.65 dBm, SINR of 16.55 dB, throughput of 1.062 Mbps, and users connected to 97%.Keywords: LTE-A, heterogen network, CADS4, Great Asia Afrika Bandung